2021
DOI: 10.1007/s40292-021-00462-w
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Renin–Angiotensin–Aldosterone System Inhibitors in COVID-19 Population

Abstract: Introduction The safety of renin–angiotensin–aldosterone system inhibitors (RAASi) among COVID-19 patients has been controversial since the onset of the pandemic. Methods Digital databases were queried to study the safety of RAASi in COVID-19. The primary outcome of interest was mortality. The secondary outcome was seropositivity improvement/viral clearance, clinical manifestation progression, and progression to intensive care units. A random-effect model was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 87 publications
(16 reference statements)
1
4
1
1
Order By: Relevance
“…Our results are in the line with the results of multiple published studies that reported that the use of RAAS inhibitors is not associated with increased short-term mortality in COVID-19 patients [17,18]. Our results that suggested a protective effect of ACEIs and ARBs are also consistent with the results of a growing number of studies that associated their use in COVID-19 patients a lower risk of mortality [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in the line with the results of multiple published studies that reported that the use of RAAS inhibitors is not associated with increased short-term mortality in COVID-19 patients [17,18]. Our results that suggested a protective effect of ACEIs and ARBs are also consistent with the results of a growing number of studies that associated their use in COVID-19 patients a lower risk of mortality [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…RAAS inhibitor use has been associated with a lower incidence of COVID-19 diagnosis and hospitalization [23,24]. Their use was also associated with increased seropositivity (formation of antibodies) and enhanced viral clearance [10,17]. However, they remain a significant risk factor for developing AKI, contrary to our results, and consequently, patients using them need careful monitoring of the renal functions [25,26].…”
Section: Discussioncontrasting
confidence: 72%
“…This study was not the first systematic review and meta‐analysis to assess the associations between RAAS inhibitor use and COVID‐19 outcomes. As of December 2021, at least 52 meta‐analyses had been conducted, 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 each of which pooled studies that have a critical risk of bias. Critical biases limit confidence in the evidence produced by these meta‐analyses as much as they do in each of the studies that t...…”
Section: Discussionmentioning
confidence: 99%
“… 6 At least 52 meta‐analyses have assessed associations between RAAS inhibitor use and COVID‐19 risk by collating parts of that body of research. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 However, little attention has been paid to selection bias, or other biases for that matter, which may distort the interaction between RAAS inhibitor use and COVID‐19.…”
mentioning
confidence: 99%
“…Atherosclerosis: decrease of PAI-1 in the vessel wall, reduced atherosclerosis progression and reduced instability of atherosclerotic plaque 39,40 MACE: reduced occurrence of stroke, MI, HF, CV mortality, death from any cause [41][42][43][44][45][46][47] Metabolic diseases: increased urinary uric acid excretion, activation of PPAR-γ, reduction of adipose tissue weight and of adipocyte size 14,31,32 Diabetes: reduction of the occurrence of new-onset diabetes, improvement of insulin sensitivity and HOMA-IR index 29,33 Chronic kidney disease: protective role toward the development of microalbuminuria, overt proteinuria, and the progression to end-stage renal disease [31][32][33][34][35][36] Side effects: reduced incidence of angioedema, cough, hypotension, syncope, and electrolyte abnormalities 52,[56][57][58] COVID-19: potential beneficial effects through vasodilatation, anti-inflammatory, anti-oxidative, and antiproliferative properties [60][61][62][63][64][65][66] Abbreviations: ACEi, angiotensin converting enzyme inhibitors; ARBs, angiotensin receptor blockers; CV, cardiovascular; HF, heart failure; HOMA-IR, homeostasis model assessment; LVH, left ventricular hypertrophy; MI, myocardial infarction; PAI-1, plasminogen activator inhibitor type-I; PPAR-γ, peroxisome proliferator-activated receptor.…”
Section: Lvh: Arbs Provide Beneficial Effects On Lvh Regression and O...mentioning
confidence: 99%